Analysis of the thermal integration between a Solid Oxide Full Cell and an ethanol reformer through a heat exchanger network - Siqueira, Igor Silva Flôres (2024)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Campus Joinville, Programa de Pós-Graduação em Engenharia e Ciências Mecânicas, Joinville, 2024.